“In-Vitro Antioxidant Activities of Aqueous and Methanol Extracts of Enicostemma littorale Blume” - Vinotha, S.; Ira, T.; Sri Ranjani, S. (Ra Journal Of Applied Research, 2018)
The total phenolic and flavonoid contents and antioxidant potential of hot aqueous and methanol extracts of whole plant of Enicostemma littorale Blume was investigated. The percentage yield of hot aqueous extractive value (36.3%) was greater than the percentage yield of hot methanol extractive value (21.8%) and the total phenolic and flavonoid contents in hot methanol extract were found to be higher than in the hot aqueous extract of Enicostemma littorale. Overall results of in-vitro antioxidant activity assays indicated that in comparison to the standard trolox, Enicostemma littorale showed low antioxidant activity in DPPH, ABTS and FRAP methods. Iron chelating activity not found at highest possible concentration of both extracts. Although the total phenolic and flavonoids components were detected in the hot methanol and aqueous extracts, these does not appear to be reported a comparison between the observed in-vitro antioxidant activity and extractive values with total phenolic and flavonoids contents of Enicostemma littorale.
Keywords: Enicostemma littorale; in- vitro antioxidant